Estimation of EVA Mode Choice Model Parameters with Different Types of Utility Functions - Maher, Tomaž; Strnad, Irena; Žura, Marijan (Promet - Traffic&Transportation, 2011)
This paper presents the estimation of nine types of utility function parameters for the application in EVA mode choice model for the city of Ljubljana, Slovenia. Four different modes (private car, public transport, bike and walking) and five purposes (work, education, shopping, leisure and other) were taken into consideration. This paper presents first the design of the Stated Preference survey, then a brief review of the EVA model, different types of utility functions and the estimation method. The final log-likelihood enables comparison of different types of utility functions. The results show that absolute differences in final log-likelihood among most types of utility functions are not high despite the different shapes, which implies that different functions may best describe different variables.